2012
DOI: 10.5539/apr.v4n1p42
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Bonding of Metals by Deposition of Nanoparticles at the Interface

Abstract: Copper nanopartices having some tens nanometer in diameter were prepared by pulsed laser ablation in a helium background gas to form active interface of copper-to-copper bonding. The nanoparticles deposited on Cu plate were annealed in hydrogen gas atmosphere. The sintering starts from below 473 K and boundary of nanoparticles was hardly observed above 673 K. Bonding of copper-to-copper metal pieces has been carried out by deposition of copper nanoparticles on the test piece as active interface followed by ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…28) In the sintering of copper fine particles, the particle size is one of the important factors because the melting point remarkably depends on the size. 29,30) It has been reported that melting points of copper nanoparticles with the sizes of 34,40,50,59, and 63 nm were 168, 202, 427, 500, and 565 °C, respectively. 29) The smaller copper particle has the lower melting point, which is advantageous to the sintering at the lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…28) In the sintering of copper fine particles, the particle size is one of the important factors because the melting point remarkably depends on the size. 29,30) It has been reported that melting points of copper nanoparticles with the sizes of 34,40,50,59, and 63 nm were 168, 202, 427, 500, and 565 °C, respectively. 29) The smaller copper particle has the lower melting point, which is advantageous to the sintering at the lower temperatures.…”
Section: Introductionmentioning
confidence: 99%